Diurnal Variations in Summer Precipitation over the Yellow River Basin - Yang Zhao; Minzhong Wang; Jiao Li; Xiaojun Yang; Nan Zhang; Hong Chen (Advances in Meteorology)
The diurnal variations in summer precipitation over the Yellow River Basin (YRB) are investigated based on the National Centers for Environmental Prediction reanalysis dataset and hourly precipitation data from 481 gauge stations over the YRB during the time period 1981–2013. Three stair steps are identified to represent the upper, middle, and lower reaches of the YRB due to complex topography elevations over the different subregions of the YRB. The summer diurnal precipitation over the YRB shows significant spatial and temporal variations. The diurnal peaks in precipitation over the upper and middle reaches of the YRB occur in the evening and late afternoon, respectively. By contrast, double peaks in diurnal precipitation occur in the early morning and late afternoon over the lower reaches of the YRB. The diurnal peaks in summer precipitation along the YRB have an eastward transition, suggested to be associated with the westerlies transporting water vapor. Differing from the increasing tendency of summer hourly precipitation from west to east across the YRB with topography elevations decreased, a distinct reduction in hourly precipitation is observed over the transition region between the first and second stair steps in the YRB. Further analysis attributes this phenomenon to the regional descending airflow induced by the steep terrain along the slope of the Tibetan Plateau (TP).